Análise técnico-econômica preliminar do processo de produção de surfactina - Magalhães, Augusto Vieira (2019)
Surfactins are lipopeptides, a class of biosurfactants, which is recently presenting substantial market growth. The molecule is a lipopeptide secreted by Bacillus subtilis strains and came into light as a promising industrial target due to its range of potential applicabilities and remarkable antimicrobial activity. Production for cosmectic market was selected due to its higher aggregated value and recent growing interest in literature. Classical process description is based on bubbling bioreactor, foam fractioning and solvent extraction, whereas technological alternatives rely on non-dispersive oxygenation using membrane contactors and ultrafiltration. Four process scenarios were defined based on the production and purification possibilities mentioned above. Four process flow diagrams were designed and 36 simulations were conducted in SuperPro Designer (Intelligen, Inc) to develop a techno-economic evaluation. A sensitivity analysis was performed using Crystal Ball (Oracle ®). Results highlighted for the first time the importance to produce above 5 t/y to assure process feasibility. Furthermore, process equipment optimization for cost reduction and the use of alternative media from renewable sources revealed minor impact on the process feasibility. Volumetric productivity was by far the most significant parameter, holding up to 80% of the process costs variability.